Factors Analysis Structure with Profitability as Intervening Variables - Nana Umdiana; Nikke Yusnita Mahardini; Irma Dewi Manurung (AKRUAL: JURNAL AKUNTANSI, 2022)
This study aims to identify and analyzes the factors that influence capital structure with profitability as an intervening variable in mining companies listed on the Indonesia Stock Exchange (IDX). The quantitative research method was used in this study. The study used 228 data for path analysis. Classical assumption test analysis, path analysis, Sobel test, and hypothesis testing using SPSS 25 statistical tools as analytical methods. The steps for testing path analysis are as follows: First, formulate a structural equation. Second Calculate the path coefficient based on the regression coefficient. Third Calculate the path coefficient simultaneously. Finally, Calculate the path coefficient simultaneously. The results of this study indicate that sales growth does not directly affect the capital structure, while firm size directly affects capital structure. At the same time, profitability cannot mediate from sales growth or company size on capital structure